Aerodynamics of a circular planform wing - Suliman, M.M. Ali; Omar, Ashraf A.; Faris, Waleed Fekry; Ismail, Ahmad Faris; Mohamed Ali, Jaffar Syed (IOP Publishing Ltd, 2019)
This paper investigates the aerodynamics of a circular plan form wing at high Reynolds numbers numerically. Commercial software STAR-CCM+ has been used for the study. The numerical results were presented in terms of flow visualization, pressure over the wing, velocity contour and streamlines, lift and drag coefficients for angle of attacks ranging from 0˚ to 30˚ and Reynolds number equal to 510,000. The results showed that the distribution of the pressure is dominated by vortices behaviour at high angle of attack. The results also show that there is a large separation region located on the trailing edge of the elevator and the cockpit region. It is evident that this type of wing configurations plays a very important role in delaying or preventing the flow separation. The result agreed with available experimental data.